Issues in halal food product labelling: a conceptual paper - Osman, Suraiya; Ab. Rahman, Suhaimi; Jalil, Abdullaah (Rynnye Lyan Resources, 2020)
The paper was aimed to uncover the issues encountered on Halal Food Product labelling to prevent the misuse of Islamic attributes in food products labelling and to ensure the appropriate trademarks, terms, and label used on the packaging and marketing strategy. The method used for this conceptual paper was from literature reviews from journal articles, thesis, proceedings and conferences, books, and online news, which are related to the keywords and research area. Trademarks and labels are among the crucial elements in marketing, which enable the consumer to differentiate the quality, the ingredients and will affect the consumers’ buying choice. Recently there is a trend of using Islamic attributes in food product labelling as trademarks to attract Muslim consumers. The issues encountered on halal food product labelling are the use of Quranic verses on the drink, the term “Sunnah food”, using Islamic terms such as “Masjid”, “Mukmin”, and others in food products’ trademark and label. The consumers were deceived into thinking that theseproducts have extra benefits as compared to others due to Islamic attributes they have.Thus, there is a need for an in-depth study on these issues since there is no clear and specific guideline on this matter.